1999
DOI: 10.1562/0031-8655(1999)070<0261:liditr>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced Damage in the Retina: Differential Effects of Dimethylthiourea on Photoreceptor Survival, Apoptosis and DNA Oxidation

Abstract: In the rat, photoreceptor cell death from exposure to intense visible light can be prevented by prior treatment with antioxidants. In this study we subjected albino rats raised in dim cyclic light and rats made more susceptible to light damage by rearing in darkness to exposures of green light that led to similar losses of photoreceptor cells. Rhodopsin and photoreceptor DNA, indicators of the number of surviving photoreceptor cells, were determined at various times over a period of 14 days after light exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
2
19
1
Order By: Relevance
“…AU). The sparing effect of DMTU observed in these experiments was even greater than that previously reported for normal albino rats treated similarly (see Organisciak et al, 1999).…”
Section: Histology and Quantitative Morphometrycontrasting
confidence: 49%
See 2 more Smart Citations
“…AU). The sparing effect of DMTU observed in these experiments was even greater than that previously reported for normal albino rats treated similarly (see Organisciak et al, 1999).…”
Section: Histology and Quantitative Morphometrycontrasting
confidence: 49%
“…Intense light exposure (retinal light damage paradigm) was performed essentially as described in detail previously (Organisciak et al, 1996(Organisciak et al, , 1999Vaughan et al, 2003). After 20-24 hr of dark adaptation, control and AY9944-treated animals were light-exposed, either at P28 or P37 (when AY9944-treated animals show little sign of retinal degeneration; Fliesler et al, 1999).…”
Section: Light Damage and Dmtu Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MP is thought to preserve foveal S-cone sensitivity, protecting it from shortwavelength blue light damage in humans (Haegerstrom-Portnoy, 1988). It has also been shown that the administration of antioxidants can prevent light-induced retinal damage in rat retinas (Organisciak et al, 1999). More recently, dietary supplementation with L in mice has been reported to suppress laser-induced CNV formation, and to inhibit the associated inflammatory and angiogenic molecules related to CNV pathogenesis (Izumi-Nagai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The SLOS rat model was produced as previously described (Fliesler et al, 2004), by treatment of Sprague Dawley (albino) rats with AY9944, a selective inhibitor of 3β-hydroxysterol-Δ 7 -reductase (Dvornik et al, 1963;Givner and Dvornik, 1965 Inc.) upon weaning; rats were provided water, ad lib, and were maintained in dim cyclic light (20-40 lux, 12 hr light-12 hr dark) at 22-25 °C, unless otherwise stated. The retinal light damage paradigm was performed essentially as previously described (Organisciak et al, 1996(Organisciak et al, , 1999Vaughan et al, 2003Vaughan et al, , 2005. Rats (6-wk postnatal age, N=4 per group) were darkadapted overnight, and then exposed for 24 hr to intense green light (1700 lux, 490-580 nm) in a temperature-controlled, Plexiglass chamber (kindly provided by D.T.…”
mentioning
confidence: 99%